History in the Playground Teaching History of Everyday Life to Ninth Graders - Sharma, Ronita (Voices of Teachers and Teacher Educators, 2019)
This paper reflects onmy experience of teaching ‘everyday life and culture’ in CBSE affiliated Schools across geographies. My documentation and analysis includes challenges of devising new strategies suitable for teaching this form of history, designing appropriate lesson plans, discussion with colleagues and peer group and finally responses of students across the schools. The idea of learning history in school puts textbook at the top authoritative position, teacher at the next position in that order of hierarchy and of course learners are the receiving end. I have shared how during the course of teaching history of cricket there were several aspects where students had an upper hand, so the usual pedagogic order and hierarchy started crumbling. Inclusion of these themes in history textbooks provided the teachers with a different opportunities towards teaching history, however it is important to underline that writing social history of everyday life marks a significant shift in history writing therefore inclusion of this theme should not be perceived merely as ‘additions.’ In this context the paperalso discusses the significant shifts in historiography which led to writing histories of everyday life.The skill of framing historical questions about ubiquitous everyday life helps to relook at history in a different light altogether and in turn historicize everyday life. It helps in breaking the popular belief that the study of history has only to do with the distant past. The history of cricket and clothing helps the learner to connect to the present and simultaneously delving deep into the past and unfolding the different layers of history. The paper finally argues that in order to realize the new possibilities of teaching history at classroom level introduction of new history textbooks should be accompanied by strong in-service teacher’s training which should familiarize teachers with major historiographical debates.